Conservative management of mandibular fractures in pediatric patients during the growing phase with splint fiber and ligature arch wire - Lifeng Li; Kiran Acharya; Bedana Ghimire; Yanqiu Li; Xiaotao Xing; Xiaoru Hou; Lingnan Hou; Xiaoyi Hu (BMC, 2023)
Abstract Purpose The purpose of this article is to discuss the effective management of mandibular fractures in pediatric patients during the growing phase of the mandible using splint fiber and ligature wire. Methods A retrospective study examined pediatric patients with mandibular fractures who were treated using the splint (Quartz) fiber and ligature wire technique at the Stomatology Hospital of Xi'an Jiaotong University from August 2021 to January 2023. Data on gender, age, location or site of the fracture, and development of tooth stage were collected from the patient's medical records. Descriptive statistics were used to analyze the data and evaluate the effectiveness of the splint (Quartz) fiber technique for treating mandibular fractures in pediatric patients. Results Out of 256 subjects, 6 pediatric patients with mandibular fractures were selected, resulting in an incidence rate of 2.34% with an equal sex ratio. Mental or symphysis fracture was the most common site for fracture in children, accounting for 100% of cases. Right mandibular angle fracture was observed in 16.7% of patients, while 50% of the group (3 individuals) suffered from left condylar fracture and 16.7% had a bilateral condylar fracture. Treatment with Quartz splint fiber and circumdental arch wiring using ligature wire was successful with no observed post-treatment complications or malocclusion. The splint fiber was worn for 30 days and the circumdental arch wiring was for the same. Healing of bone fracture yields good results after 12 weeks. Follow-up care is crucial to monitor for complications, in this study, no post-treatment complications were observed. Conclusion The treatment of pediatric mandibular fractures is complex and requires careful consideration of various factors. Conservative management should be the first choice, with open reduction and internal fixation reserved for specific cases. The use of quartz splint fiber and ligature wire is an effective treatment option for stabilizing the mandible and providing occlusal stability in growing children. A fiber splint along with ligature wire can also be used as an alternative treatment to avoid any adverse effects on the growth and development of the mandible and permanent teeth. A multidisciplinary approach is essential to achieving the best outcomes for pediatric patients with mandibular fractures.